The Effect of Self-Efficacy Mediation on Entrepreneurship Education and Entrepreneurial Intention - Hafid, Radia; Santoso, Ivan Rahmat; Gani, Imam Prawiranegara (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2024)
This study aims to investigate the effect of entrepreneurship education on entrepreneurial intention mediated by self-efficacy. It employed a quantitative approach with a sample of 175 students majoring in economics at Universitas Negeri Gorontalo (UNG). The study used primary and secondary data from observation, questionnaire, and documentation methods. The data analysis technique uses SEM-PLS 4 to test the relationship between variables. The study findings signify that entrepreneurship education’s effect is significant to entrepreneurial self-efficacy and intention. Entrepreneurial self-efficacy is significantly and positively related to entrepreneurial intention and completely mediates between entrepreneurial education and intention. Theoretically, this study contributes to education and entrepreneurial intentions. Then, this study provides practical implications for teachers to focus on creating entrepreneurial opportunities and platforms for students to improve their experiences.